2010
DOI: 10.1021/bi101069u
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Molecular Activity of Alkaline Sphingomyelinase (NPP7) by Computer Modeling

Abstract: The enzymes in the nucleotide pyrophosphatase/phosphodiesterase (NPP) family have various substrates such as nucleotides, phospholipids, and sphingolipids. The substrate specificity in relation to their structures is largely unknown because no mammalian NPP complex has been crystallized. NPP7, also called alkaline sphingomyelinase (alk-SMase), is a NPP family member that may have important implications in carcinogenesis and cholesterol absorption. The sequence of NPP7 is 36% similar to that of the closest NPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…This interaction site was previously described by Duan, et al , in their modeling study on NPP7. [15] They found that an F275G mutant showed almost no sphingomyelinase activity, consistent with our reduced activity of the F275A mutant. Perhaps surprisingly, an alignment of the mammalian NPP enzymes shows remarkable variability in the residue types that align with F275.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This interaction site was previously described by Duan, et al , in their modeling study on NPP7. [15] They found that an F275G mutant showed almost no sphingomyelinase activity, consistent with our reduced activity of the F275A mutant. Perhaps surprisingly, an alignment of the mammalian NPP enzymes shows remarkable variability in the residue types that align with F275.…”
Section: Discussionsupporting
confidence: 83%
“…Due to the much smaller gap-aligned segments in the 2GSO-based model of hNPP7, this model was used in all docking studies with substrates. Two prior modeling studies of hNPP7 also used a crystallographic structure of the bacterial NPP as the modeling template [15,24], although one of the studies was published prior to the availability of the NPP2 crystal structures [15]. The insertion of residues in the NPP7 sequence within the segment interacting with LPA in NPP2 limits the utility of the NPP2 crystal structures as templates even though they share a common substrate with NPP7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whereas other members of the AP superfamily transfer an unsubstituted phosphoryl group (−PO 3 2− ) and donate hydrogen bonds to both of the nonbridging phosphoryl oxygen atoms of monoester substrates, NPP transfers a substituted phosphoryl group (−PO 2 OR′ − ) and has a substituent binding pocket that interacts with the R′ substituent attached to one of the phosphoryl oxygen atoms of its diester substrates (Figure 1). 17,2224 This pocket functionally replaces one set of hydrogen bonds that provide favorable interactions with monoester substrates in the monoesterase members of the superfamily. Depending on the architecture of the pocket, substrates for enzymes in the NPP family can be nucleotides or lipids, such as choline phosphoesters, and sphingomyelin.…”
mentioning
confidence: 99%